Improved inhibition of telomerase by short twisted intercalating nucleic acids under molecular crowding conditions - Agarwal, Tani; Pradhan, Devranjan; Geci, Imrich; El-Madani, Amro M.; Petersen, Michael; Pedersen, Erik B.; Maiti, Souvik (Nucleic Acid Therapeutics, 2012)
Human telomeric DNA has the ability to fold into a 4-stranded G-quadruplex structure. Several G-quadruplex ligands are known to stabilize the structure and thereby inhibit telomerase activity. Such ligands have demonstrated efficient telomerase inhibition in dilute conditions, but under molecular crowding conditions mimicking physiological milieu, stabilization of the telomeric G-quadruplex is often lost. We attempted to demonstrate the enhanced G-quadruplex stabilizing ability under molecular conditions by using twisted intercalating nucleic acids (TINA)-modified oligonucleotides. We have shown using circular dichroism and ultraviolet spectroscopic methods that these TINA-modified short oligonucleotides function as G-quadruplex, inducing agents and participate in the formation of stabilized 3:1 G-quadruplex with the human telomeric oligonucleotide. Using enzyme-linked immunosorbent assay-based telomerase repeat amplification assay (TRAP) assay as well as nondenaturing polyacrylamide gel electrophoresis-based TRAP, we demonstrate remarkable enhancement in their anti-telomerase activity even under molecular crowding conditions. This is the first time in which a G-quadruplex stabilizing agent has demonstrated enhanced activity even under molecular crowding conditions.

In the sense of transcription regulation by G-quadruplexes: asymmetric effects in sense and antisense strands - Agarwal, Tani; Roy, Saumya; Kumar, Santosh; Chakraborty, Tushar Kanti; Maiti, Souvik (Biochemistry, 2014)
G-Quadruplexes occupy important regulatory regions in the genome. DNA G-quadruplexes in the promoter regions and RNA quadruplexes in the UTRs (untranslated regions) have been individually studied and variously implicated at different regulatory levels of gene expression. However, the formation of G-quadruplexes in the sense and antisense strands and their corresponding roles in gene regulation have not been studied in much detail. In the present study, we have elucidated the effect of strand asymmetry in this context. Using biophysical methods, we have demonstrated the formation of stable G-quadruplex structure in vitro using CD and UV melting. Additionally, ITC was employed to demonstrate that a previously reported selective G-quadruplex ligand was able to bind and stabilize the G-quadruplex in the present sequence. Further, we have shown using reporter constructs that although the DNA G-quadruplex in either strand can reduce translation efficiency, transcriptional regulation differs when G-quadruplex is present in the sense or antisense strand. We demonstrate that the G-quadruplex motif in the antisense strand substantially inhibits transcription, while when in the sense strand, it does not affect transcription, although it does ultimately reduce translation. Further, it is also shown that the G-quadruplex stabilizing ligand can enhance this asymmetric transcription regulation as a result of the increased stabilization of the G-quadruplex.

Morphological effects of G-quadruplex stabilization using a small molecule in zebrafish - Agarwal, Tani; Lalwani, Mukesh Kumar; Kumar, Santosh; Roy, Saumya; Chakraborty, Tushar Kanti; Sivasubbu, Sridhar; Maiti, Souvik (Biochemistry, 2014)
Zebrafish (Danio rerio) embryos are transparent and advantageous for studying early developmental changes due to ex utero development, making them an appropriate model for studying gene expression changes as a result of molecular targeting. Zebrafish embryos were injected with a previously reported G-quadruplex selective ligand, and the phenotypic changes were recorded. We report marked discrepancies in the development of intersegmental vessels. In silico analysis determined that the putative G-quadruplex motif occur in the upstream promoter region of the Cdh5 (N-cadherin) gene. A real-time polymerase chain reaction-based investigation indicated that in zebrafish, CDH-2 (ZN-cad) was significantly downregulated in the ligand-treated embryos. Biophysical characterization of the interaction of the ligand with the G-quadruplex motif found in this promoter yielded strong binding and stabilization of the G-quadruplex with this ligand. Hence, we report for the first time the phenotypic impact of G-quadruplex targeting with a ligand in a vertebrate organism. This study has unveiled not only G-quadruplex targeting in non-human animal species but also the potential that G-quadruplexes can provide a ready tool for understanding the phenotypic effects of targeting certain important genes involved in differentiation and developmental processes in a living eukaryotic organism.